Proportion of HIV exposed infants aged 0-6 months that missed nevirapine prophylaxis in Mulago National Referral Hospital, Uganda: a cross-sectional study - Nasambu Hellen; Rujumba Joseph; Mupere Ezekiel; Semitala Fred; Senyonga Ronald; Musoke Philippa (BMC Pediatrics)
Abstract Background Nevirapine prophylaxis has been found to lower the risk of HIV transmission in breastfed infants. While about 95% of HIV positive pregnant and lactating mothers use Antiretroviral therapy in Uganda, a smaller percentage of HIV exposed infants (HEI) receive nevirapine (NVP) prophylaxis. This study aimed to determine the proportion of HEI who missed NVP prophylaxis and associated factors. Methods This was a cross-sectional study done using quantitative methods, conducted at Mulago National Referral Hospital (MNRH). A total of 228 mother-infant pairs were enrolled. The proportion of HEI who missed NVP, maternal, infant and health facility factors associated were determined using a pre-tested questionnaire. Bivariate analysis and binary logistic regression model were used to determine the proportion and factors associated with missing NVP prophylaxis. Results The proportion of HEI who missed NVP prophylaxis was 50/228 (21.9%). Factors significantly associated with HEI missing NVP prophylaxis included delivery from outside government health facilities (AOR = 8.41; P = 0.001), mothers not undergoing PMTCT counselling (AOR = 12.01; P = 0.001), not on ART (AOR = 8.47; P = 0.003) and not having disclosed their HIV status to their partners (AOR = 2.80; P = 0.001). The HEI that missed nevirapine and were HIV positive were 35 (70.0%). The HEI that were HIV infected despite receiving nevirapine prophylaxis were 5 out of 40(12.5%). Conclusion One in five HEI missed NVP prophylaxis and nearly three quarters of those who missed NVP prophylaxis were HIV infected. Improving uptake of nevirapine by HEI will require interventions that can aid to strengthen PMTCT counselling.